To little, too late? Rice production to mitigate climate change in Colombia - Andrade, R.; Generale, Giovanni; Ibarra, L.; Esponda, M.; Romero Sánchez, Miguel Antonio; Gonzalez, C. (2023)
The adoption of better technological practices make rice production more resilient. These results demonstrate the pivotal role of agroclimatic forecasting and extension services to mitigate the effects of climate change on rice production. Better measurements of GHG emissions and computation of site-specific emissions are crucial to clearly identify the effects of adaptation and mitigation initiatives.